Effect of Solution Silicate on the Precipitation of Barium Sulfate - Jones, Franca; Radomirovic, Tomoko; Ogden, Mark (American Chemical Society, 2012)
The presence of silicate during barium sulfate crystallization has different impacts depending on the pH of the solution. At pH 7 the dominance of the protonated form (H4SiO4) and possible polymerization of the silicate impacts mainly on the aggregation state and on twinning of the barium sulfate formed. At higher pH values (10), the silicate ion present is able to influence both morphology and partially substitute for sulfate in the lattice. Interesting fibrous particles are formed under these conditions, but this is not due to mesocrystal formation as the particles are observed to be single crystalline in nature. These fibrous sections are found to be dominant on the surface and are highly porous. These particles are different, however, to the biomorphs formed when crystallization of barium carbonate occurs in the presence of silicate. This is because the speciation of sulfate does not change over a large pH range. The impact of silicate on barium sulfate particles is similar to the impact on calcium carbonate and strontium sulfate crystallization.